Difficult Airway Management in Neonates and Infants: Knowledge of Devices and a Device-Oriented Strategy - Sawa, Teiji; Kainuma, Atsushi; Akiyama, Koichi; Kinoshita, Mao; Shibasaki, Masayuki (Frontiers in Pediatrics, 2021)
Difficult airway management (DAM) in neonates and infants requires anesthesiologists and critical care clinicians to respond rapidly with appropriate evaluation of specific situations. Therefore, organizing information regarding DAM devices and device-oriented guidance for neonate and infant DAM treatment will help practitioners select the safest and most effective strategy. Based on DAM device information and reported literature, there are three modern options for DAM in neonates and infants that can be selected according to the anatomical difficulty and device-oriented strategy: 1) video laryngoscope (VLS), 2) supraglottic airway device (SAD), and 3) flexible fiberoptic scope (FOS). Some VLSs are equipped with small blades for infants. Advanced SADs have small sizes for infants, and some effectively function as conduits for endotracheal intubation. The smallest FOS has an outer diameter of 2.2 mm and enables intubation with endotracheal tubes with an inner diameter of 3.0 mm. DAM in neonates and infants can be improved by effectively selecting the appropriate device combination and ensuring that available providers have the necessary skills.